Enhanced estimates of carcass and meat quality effects for polymorphisms in myostatin and µ-calpain genes, ,. (9th December 2018) - Bennett, Gary L; Tait, Richard G; Shackelford, Steven D; Wheeler, Tommy L; King, David A; Casas, Eduardo; Smith, Timothy P L
Abstract: The objective of this study was to enhance estimates of additive, dominance, and epistatic effects of marker polymorphisms on beef carcass and quality traits. Myostatin ( MSTN ) F94L SNP and the µ-calpain ( CAPN1 ) 316 and 4751 SNP haplotype have previously been associated with fat and muscle traits in beef cattle. Multiyear selection in a composite population segregating these polymorphisms increased minor allele (F94L L) and chosen haplotype ( CAPN1 CC and GT) frequencies to intermediate levels resulting in more precise estimates of additive and nonadditive genetic effects. During the 3 yr after selection, 176 steers were evaluated for growth, carcass, meat quality, tenderness ( n = 103), and meat color traits. The statistical model included year, age of dam, age of the steer, and genotype in a random animal model. The 9 genotypes (3 CAPN1 diplotypes × 3 F94L genotypes) affected marbling score, ribeye area, adjusted fat thickness, vision yield grade (all P < 0.001), slice shear force ( P = 0.03), and CIE L* reflectance ( P = 0.01). Linear contrasts of the 9 genotypes estimated additive, recessive, and epistatic genetic effects. Significant additive effects of the F94L L allele decreased marbling score, adjusted fat thickness, vision yield grade, and slice shear force; and increased ribeye area and CIE L* reflectance. The homozygous F94L FF and LL genotypes differed by 1.3 to 1.9 phenotypic SD for most carcass traits and by 0.8 to 0.9 SD for slice shear force and CIE L * reflectance but carcass weight differed by only 3 kg (0.1 SD). The L allele was partially recessive to F for ribeye area ( P = 0.02) and the heterozygous FL means tended to be closer to the FF genotype than the LL genotype for other carcass traits but differences from additive were not significant. The CAPN1 additive × F94L additive effect on slice shear force was the only significant epistatic estimate. The F94L L allele is prevalent in Limousin but nearly absent in other U.S. purebreds. This allele had about half of the effects on birth weight, muscle, and fat traits reported for severe MSTN mutations in Belgian Blue and Piedmontese breeds. The interaction between MSTN and CAPN1 genotypes may reflect the strong additive effects of MSTN F94L L allele on fat and muscle traits interfering with the phenotypic effect of CAPN1 genotype on meat tenderness.